An Analysis Conversation Gambits Used by Fourth Semester of English Education Program at Nurul Huda University - Zulaikah; Hikmahwati; M Zainuddin Afas (Darussalam English Journal (DEJ), 2023)
This research was carried out to determine the types and functions of gambits used by fourth semester students of English Education program. The objective of the study was to know what are the types of conversation gambits used in classroom discussion. This research used qualitative descriptive. The data of this research had been collected by way of the use of video recording. The data turned into analyzed in three principal there were: data redaction, data display and conclusion. The end result of this research discovered there were three types of gambits uttered by fourth semester of English Education program in classroom discussion, particularly: opening gambits, linking gambits, and responding gambits, and every types of gambits have different functions. The first function of opening gambits which includes asking information, breaking in, act in order, telling the story and personal person. The second function of gambits there were give reason, illustring your point and hesitation phrase. The last function of gambits there were right and wrong, showing interest, communication control, and accepting complete